(untitled) (Journal of Naval Architecture and Marine Engineering, 2025)
Many marine vessels and small unmanned air vehicles operate at low Re flow regimes. Due to their small size and low operational velocities, they face increased stall severity, which is a crucial challenge to overcome. Tubercle Leading Edge (TLE) aerofoils can be exploited to solve this issue. Akin to passive flow control devices, tubercles generate counter-rotating vortex pairs on aerofoils, with vorticity being proportional to amplitude to wavelength ratio thus augmenting lift, and delaying flow separation. Performance improvements such as reduced drag, reduced stall severity, and improved post-stall characteristics are achieved using TLE designs. This investigation experimentally and numerically is focused on the performance characteristics of three designed TLE aerofoils at a relatively low Re value of 1x105. Limited studies are available on this low Re flow regime, hence the novelty of this investigation. The aims were to build upon the literature and to determine the best TLE aerofoil variant for further investigation, development, and eventual system-level implementation in a small naval or air vehicle design. The TLE aerofoil models investigates, ‘A4λ25’, ‘A8λ25’, and ‘A12λ25’ which specify the tubercle amplitude and wavelength in mm delivered weaker and delayed stall, reduced pre-stall drag, and improved post-stall lift. The ‘A4λ25’ model offered the best combination of increased pre-stall lift, reduced pre-stall drag, and post-stall lift. Further investigation on the ‘A4λ25’ variant’s performance within the context of an engineered system is worthwhile for realizing its application in low Re flight. Journal of Naval Architecture and Marine Engineering, 22(1), 2025, PP. 1-19